A biobased polyester latex glove and a method of making the same

CN122898115APending Publication Date: 2026-10-13BEIJING CHEM IND GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610786196.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]本发明旨在解决现有一次性防护手套材料依赖化石资源、存在过敏风险以及废弃后难以降解等技术问题,本发明基于“共聚内增韧”和“交联网络增强”相结合的策略,提供一种以生物基单体为主要原料的新型生物基聚酯弹性体制备得到的乳胶手套,其具有高性能、低致敏性、环境友好

Benefits of technology

本发明成功地将生物基聚酯和成熟的工业生产技术相结合,制备得到一种性能优越、绿色环保、安全低敏的新一代防护手套产品,具有广阔的市场前景和重要的社会价值。具体地:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898115A_ABST
    Figure CN122898115A_ABST
Patent Text Reader

Abstract

The application discloses a kind of bio-based polyester latex gloves and preparation method thereof.The raw material of the bio-based polyester latex gloves of the application includes emulsifier, crosslinking agent and the polyester containing the structural unit shown in formula (I).The application successfully combines bio-based polyester and mature industrial production technology, and a new generation of protective gloves product with superior performance, green environmental protection, safety and low sensitivity is prepared, which has broad market prospect and important social value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a bio-based polyester latex glove and its preparation method. Background Technology

[0002] Disposable protective gloves are indispensable consumables in fields such as medical care, food processing, electronics manufacturing, and daily protection. Currently, the mainstream disposable gloves on the market are mainly made of materials such as natural latex, nitrile rubber, and polyvinyl chloride (PVC).

[0003] While natural latex gloves offer excellent elasticity and comfort, the latex proteins they contain are common allergens, potentially triggering severe allergic reactions (Type I hypersensitivity) in some users. Nitrile rubber gloves, as a major alternative to natural latex, effectively avoid latex protein allergies and possess excellent oil and chemical resistance. However, the monomers of nitrile rubber (such as butadiene and acrylonitrile) are primarily derived from petrochemicals, and their production process relies on non-renewable fossil resources, resulting in a high carbon footprint that contradicts the current global advocacy for carbon neutrality and sustainable development. Furthermore, the vulcanization accelerators used in the production of nitrile rubber (such as thiurams and thiazoles) may cause contact dermatitis (Type IV hypersensitivity) in some individuals. PVC gloves, while inexpensive, have poor elasticity and comfort, and the plasticizers used in their production (such as phthalates) pose potential health risks and environmental pollution problems. Additionally, all of the above glove materials are difficult to degrade after disposal, creating significant "white pollution" pressure on the environment.

[0004] With the development of biomass conversion technology, the preparation of polymer materials using renewable biological resources has become a research hotspot. Bio-based polymers, such as polylactic acid (PLA), polyhydroxyalkanoates (PHA), and polybutylene succinate (PBS), have attracted much attention due to their renewable and biodegradable properties. However, most existing bio-based polyester materials suffer from insufficient flexibility, poor elasticity, and low mechanical strength, making it difficult to directly meet the stringent requirements of protective gloves for high strength, high elongation, and excellent resilience. For example, although PLA has high hardness, it is brittle and has extremely low elongation at break; although PBS has good flexibility, its modulus and strength still cannot compare with nitrile rubber.

[0005] Therefore, developing a novel glove material derived from renewable resources, possessing excellent mechanical properties (especially high elasticity and high strength), good biocompatibility (low allergenicity), and biodegradability potential to replace traditional petroleum-based glove materials has significant socio-economic benefits and environmental significance. Summary of the Invention

[0006] This invention aims to solve the technical problems of existing disposable protective glove materials, such as reliance on fossil resources, the risk of allergies, and difficulty in degradation after disposal. Based on a strategy combining "copolymer internal toughening" and "crosslinking network reinforcement", this invention provides a new type of latex glove made from bio-based polyester elastomer with bio-based monomers as the main raw material. It has high performance, low allergenicity, and environmental friendliness.

[0007] To achieve the above objectives, the technical solution provided by the present invention is as follows: A bio-based polyester latex glove, wherein the raw materials of the bio-based polyester latex glove include an emulsifier, a crosslinking agent, and polyester containing structural units shown in formula (I): (I) U1, U2, U3, and U4 may be the same or different, and are independently selected from C1, U2, U3, and U4, which are chemically bonded, unsubstituted, or substituted by at least one group represented by formula (A). 1-10 alkylene, unsubstituted, or substituted with at least one group of formula (A) 2-10 alkenyl; (A) Each Q may be the same or different, and each is independently selected from chemical bonds or C. 1-10 Alkylene; Each R m They are the same or different, and are selected independently from H or C. 1-10 alkyl; Each R n They are the same or different, and are selected independently from H or C. 1-10 alkyl; Z1, Z2, Z3, and Z4 may be the same or different, and are independently selected from chemical bonds or C bonds. 1-10 Alkylene; Represents chemical bonds; 'a' represents a number from 6 to 30; b represents a number between 8 and 35; c represents a number from 16 to 65; d represents a number from 0 to 5; The condition is that two, three, or four of U1, U2, U3, and U4 are selected from C1, U2, U3, and U4 that are unsubstituted or substituted by at least one group represented by formula (A). 2-10 It is an alkenyl group, and at most one of U1, U2, U3 and U4 is a chemical bond.

[0008] According to an embodiment of the present invention, the emulsifier is selected from, but not limited to, one, two, or more of sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, and polyethylene glycol octylphenyl ether.

[0009] According to an embodiment of the present invention, the crosslinking agent is selected from, but not limited to, at least one of dicumyl peroxide and 2,4-di-tert-butyl peroxide.

[0010] According to an embodiment of the present invention, the weight ratio of the polyester, emulsifier and crosslinking agent is 10:(0.1~0.5):(0.005~1), preferably 10:(0.2~0.4):(0.005~1), for example 10:0.2:0.05, 10:0.2:0.1, 10:0.3:0.1, 10:0.4:0.2, 10:0.4:0.5, 10:0.4:1.

[0011] According to an embodiment of the present invention, the structural unit shown in formula (I) has the structure shown in formula (II): (II) Among them, Y1, Y2, Y6, Y7, Y8, and Y9 are the same or different, and are independently selected from C. 1-10 Alkylene; Y3, Y4, and Y9 may be the same or different, and are independently selected from chemical bonds, C... 1-10 Alkylene or C 2-10 alkenyl; Y5 is selected from C 1-10 Mesenchymal or carbon atom; Y6 is selected from C 1-10 Alkylene or C 1-10 Phenyl group; Indicates a single or double bond, provided that when When representing a single bond, Y5 is C. 1-10 Phenylene group, Y6 is C 1-10 alkylene; when When representing a double bond, Y5 represents a carbon atom and Y6 represents a carbon atom. 1-10 Phenyl group; Z1, Z2, Z3, and Z4 may be the same or different, and are independently selected from chemical bonds or C bonds. 1-10 Alkylene; R1, R2, R3, and R4 may be the same or different, and are independently selected from H or C. 1-10 alkyl; Q1 is selected from chemical bonds or C. 1-10 Alkylene; Each R a They are the same or different, and are selected independently from H or C. 1-10 alkyl; Each R b They are the same or different, and are selected independently from H or C. 1-10 alkyl; R5 and R6 may be the same or different, and are independently selected from H and C. 1-10 Alkyl groups or groups represented by formula (B): (B) Q2 is selected from chemical bonds or C. 1-10 Alkylene; Each R c They are the same or different, and are selected independently from H or C. 1-10 alkyl; Each R d They are the same or different, and are selected independently from H or C. 1-10 alkyl; Represents chemical bonds; 'a' represents a number from 6 to 30; b represents a number between 8 and 35; c represents a number from 16 to 65; d represents a number from 0 to 5.

[0012] According to an embodiment of the present invention, the polyester further comprises a structural unit as shown in formula (III): (III) Among them, Alk1, Alk2, and Alk3 may be the same or different, and are independently selected from C. 1-12 Alkylene.

[0013] Preferably, the polyester comprises the structural unit shown in formula (D) and the structural unit shown in formula (E): (D) (E) Among them, D1, D2, D3, E1, E2, and E3 are the same or different, and are independently selected from C. 1-12 Alkylene; The condition is that one, two, or three of the following conditions are met: (1) D1 and E1 are not the same; (2) D2 and E2 are not the same; (3) D3 and E3 are not the same.

[0014] According to an embodiment of the present invention, the polyester is obtained by a reaction between a saturated diol, a saturated diacid, and a molecular structure modifier; wherein the molecular structure modifier is selected from a double-terminated hydroxyl telechelic polymer containing C=C bonds.

[0015] Preferably, the polyester has structural units represented by formula (I) as described above (such as structural units represented by formula (II), (i), (ii) or (iii); and structural units represented by formula (III) (such as structural units represented by formula (D) and formula (E)).

[0016] According to an embodiment of the present invention, the reaction between the saturated diol, the saturated diacid, and the molecular structure modifier is an esterification reaction and a polycondensation reaction.

[0017] According to an embodiment of the present invention, the C=C bond-containing dual-hydroxyl telechelic polymer is selected from one of dual-hydroxyl polybutadiene (HTPB), dual-hydroxyl polyisoprene, and dual-hydroxyl myrcene, preferably dual-hydroxyl polybutadiene.

[0018] According to embodiments of the present invention, the hydroxyl values ​​of the C=C-terminated hydroxyl telechelic polymers are the same or different, and are independently selected from 0.1-1 mmol / g, for example 0.47-0.53 mmol / g, 0.54-0.64 mmol / g, 0.65-0.70 mmol / g or 0.71-0.80 mmol / g.

[0019] According to an embodiment of the present invention, the saturated diol is selected from at least two of ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol, preferably 1,2-propanediol and 1,4-butanediol.

[0020] According to an embodiment of the present invention, the saturated dicarboxylic acid is selected from at least two of succinic acid, glutaric acid, adipic acid, and sebacic acid, preferably 1,6-adipic acid and 1,10-sebacic acid.

[0021] According to an embodiment of the present invention, the molar ratio of the total molar amount of -OH in the saturated diol and the C=C-terminated hydroxyl telechelic polymer to the molar amount of -COOH in the saturated dicarboxylic acid is (1.05~1.8):1.

[0022] According to an embodiment of the present invention, the amount of -OH in the C=C-containing double-terminated hydroxyl telechelic polymer is 0.1% to 1.0% of the total molar number of -OH in the saturated diol and the C=C-containing double-terminated hydroxyl telechelic polymer, preferably 0.15% to 0.50%.

[0023] According to an embodiment of the present invention, the C=C double bond content in the polyester is 0.5 mol% to 15.0 mol%, preferably 0.9 mol% to 10 mol%, more preferably 0.9 mol% to 5.0 mol%, for example, 1 mol%, 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, or any two of the above values.

[0024] According to an embodiment of the present invention, an antioxidant and a polymerization inhibitor are also added during the esterification reaction.

[0025] According to an embodiment of the present invention, the antioxidant is selected from one or two of antioxidant 1010, antioxidant 245, phosphoric acid, phosphorous acid, and phosphate ester.

[0026] According to an embodiment of the present invention, the amount of antioxidant used is 0.01% to 0.6% of the total mass of diol and diacid, preferably 0.01% to 0.2%.

[0027] According to an embodiment of the present invention, the polymerization inhibitor is selected from at least one of hydroquinone, benzoquinone, tetrachlorobenzoquinone, 1,3,5-trinitrobenzene, and 1,1-diphenyl-2-trinitrobenzylhydrazine.

[0028] According to an embodiment of the present invention, the amount of the polymerization inhibitor is 0.01% to 0.6% of the total mass of the diol and diacid, preferably 0.01% to 0.2%.

[0029] According to an embodiment of the present invention, a catalyst is also added during the polycondensation reaction.

[0030] According to an embodiment of the present invention, the catalyst is selected from titanium-based catalysts, antimony-based catalysts, and tin-based catalysts, such as at least one of tetrabutyl titanate, tetraisopropyl titanate, antimony trioxide, stannous octoate, and stannous chloride.

[0031] According to an embodiment of the present invention, the amount of catalyst used is 0.05% to 1.5% of the total mass of the diol and the dicarboxylic acid, for example, 0.1%, 0.5%, 1% or any two of the above values.

[0032] According to an embodiment of the present invention, the number average molecular weight (Mn) of the polyester is not less than 10,000, for example, 10,000, 12,000, 14,000, 16,000, 18,000, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000, 50,000 or a range between any two of the above values.

[0033] According to an embodiment of the present invention, the weight-average molecular weight (Mw) of the polyester is not less than 20,000, for example, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000, 50,000, 55,000, 60,000, 70,000, 80,000, 90,000 or a range between any two of the above values.

[0034] According to an embodiment of the present invention, the polydispersity index (PDI) of the polyester is less than 5, preferably 1 to 3, for example 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or any two of the above values.

[0035] According to an embodiment of the present invention, the glass transition temperature of the polyester is -25°C to -60°C.

[0036] According to an embodiment of the present invention, the polyester is a bio-based polyester, which is prepared using at least one bio-based source raw material. Preferably, one, two, or all of the saturated diol, saturated diacid, and molecular structure modifier are bio-based.

[0037] According to an embodiment of the present invention, the polyester is an elastomer, preferably a bio-based polyester elastomer.

[0038] The present invention also provides a method for preparing the above-mentioned bio-based polyester latex gloves, the method specifically including the following steps: (S1) Preparation of bio-based polyester latex: Polyester is dissolved in an organic solvent to prepare a polymer solution with a mass fraction of 15%~40%; emulsifier, crosslinking agent and water are added to the polymer solution for pre-emulsification treatment, followed by homogenization treatment, and then the organic solvent is removed to obtain bio-based polyester latex. (S2) Hand mold impregnation with coagulant: Immerse the hand mold in a coagulant solution with a temperature of 50~70℃ and a mass fraction of 10%~30%, leave it for a few seconds, then slowly remove it and dry it in an oven at 70~90℃ to form a coagulant coating on the surface of the hand mold. (S3) Impregnating latex: The hand mold with coagulant coating in step (S3) is impregnated in the bio-based polyester latex of step (S2) for 5~20 seconds and then slowly removed. After leveling, gelling and pre-curing, a film is obtained. (S4) After removing water-soluble impurities from the adhesive film, heat setting and curing are performed, and the bio-based polyester latex gloves are obtained by demolding.

[0039] According to an embodiment of the present invention, in step (S1), the polyester is obtained by reacting a saturated diol, a saturated diacid, and a molecular structure modifier.

[0040] Preferably, the method for synthesizing the polyester specifically includes the following steps: (A1) Saturated diol, saturated diacid, molecular structure modifier, antioxidant, and polymerization inhibitor are mixed and esterified in an inert atmosphere. (A2) After the esterification reaction is completed, a catalyst is added under an inert atmosphere, the temperature is raised to the temperature of the polycondensation reaction, and the polycondensation reaction is carried out under vacuum to obtain the polyester.

[0041] According to embodiments of the present invention, the saturated diol, saturated dicarboxylic acid, molecular structure modifier, antioxidant, polymerization inhibitor, and catalyst described above have the meanings as stated above.

[0042] According to an embodiment of the present invention, in step (A1), the esterification reaction is carried out under normal pressure.

[0043] According to an embodiment of the present invention, in step (A1), the inert atmosphere refers to an atmosphere that is inert to the reaction, such as N2.

[0044] According to an embodiment of the present invention, in step (A1), the temperature of the esterification reaction is 160~200℃, preferably 170~190℃; the time of the esterification reaction is 2~4 h, preferably 2.5~3.5 h.

[0045] According to an embodiment of the present invention, in step (A2), the temperature of the polycondensation reaction is 200~240℃, preferably 210~230℃; the time of the polycondensation reaction is 2~10 h, preferably 3~8 h.

[0046] According to an embodiment of the present invention, in step (A2), the polycondensation reaction is carried out under a vacuum. A vacuum state known in the art can be selected, for example, a pressure below 800 Pa, preferably below 500 Pa.

[0047] According to an embodiment of the present invention, in step (A2), during the polycondensation reaction, small molecules and water are removed from the system.

[0048] According to an embodiment of the present invention, in step (A2), after the polycondensation reaction is completed, the polyester is collected, and a method known in the art can be used for collection; for example, an inert gas is introduced to expel the polyester from the reaction apparatus.

[0049] According to an embodiment of the present invention, in step (S1), the mass fraction of the polymer solution is preferably 15-30%, for example, 16%, 17%, 18%, 19%, 20%, 25%, 30%, or any two of the above values.

[0050] According to an embodiment of the present invention, in step (S1), the organic solvent is selected from, but not limited to, one, two or more of dichloromethane, trichloromethane, and tetrahydrofuran.

[0051] According to an embodiment of the present invention, in step (S1), the emulsifier is selected from, but not limited to, one, two or more of sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, and polyethylene glycol octylphenyl ether.

[0052] According to an embodiment of the present invention, in step (S1), the crosslinking agent is selected from, but not limited to, at least one of dicumyl peroxide and 2,4-di-tert-butyl peroxide.

[0053] According to an embodiment of the present invention, in step (S1), the weight ratio of polyester to emulsifier is 10:(0.1~0.5), preferably 10:(0.2~0.4), for example 10:0.2, 10:0.3, or 10:0.4.

[0054] According to an embodiment of the present invention, in step (S1), the weight ratio of polyester, organic solvent and water is 10:(30~100):(10~100), preferably 10:(40~50):(20~50), for example 10:40:50, 10:45:50, 10:50:50.

[0055] According to an embodiment of the present invention, in step (S1), the mass ratio of the crosslinking agent to the polyester is 0.005-1:10, for example, 0.01:10, 0.02:10, 0.03:10, 0.04:10, 0.05:10, 0.1:10, 0.2:10, 0.3:10, 0.4:10, 0.5:10, 0.6:10, 0.7:10, 0.8:10, 0.9:10, or a range between any two of the above values.

[0056] According to an embodiment of the present invention, in step (S1), the water is preferably deionized water.

[0057] According to an embodiment of the present invention, step (S1) of the pre-emulsification treatment specifically includes: preparing an emulsifier aqueous dispersion by mixing water, an emulsifier, and a crosslinking agent; and adding a polymer solution dropwise to the emulsifier aqueous dispersion under high-speed stirring to perform pre-emulsification and obtain a primary emulsion. Preferably, the high-speed stirring can be performed using methods known in the art, such as in a high-speed dispersion homogenizer, with a stirring speed of 1000-10000 rpm, for example, 5000 rpm.

[0058] According to an embodiment of the present invention, in step (S1), the homogenization process specifically includes: passing the pre-emulsified primary emulsion through a high-pressure homogenizer and cyclically processing it 1 to 3 times under a pressure of 50 to 100 MPa to form a stable and uniform emulsion.

[0059] According to an embodiment of the present invention, step (S1) of removing organic solvent specifically includes: removing organic solvent from the homogenized emulsion under 40~60 °C and reduced pressure.

[0060] According to an embodiment of the present invention, in step (S1), after removing the organic solvent, post-treatment can be performed. Preferably, the post-treatment includes adjusting the pH value to 8.0~10.0.

[0061] According to an embodiment of the present invention, in step (S1), water is optionally added to adjust the solid content of the bio-based polyester latex, for example, 30% to 50%.

[0062] According to an embodiment of the present invention, in step (S2), the hand mold may also undergo pretreatment known in the art, for example: the hand mold is sequentially acid-washed, alkali-washed and water-washed to remove surface dirt, and then dried in an oven at 80~120 °C for later use.

[0063] According to an embodiment of the present invention, the coagulant solution comprises a calcium salt and water. Preferably, the calcium salt is selected from calcium nitrate or calcium chloride.

[0064] According to an embodiment of the present invention, the impregnation temperature is 20~30 °C. In the present invention, the final thickness of the latex glove can be adjusted by controlling the impregnation time and latex viscosity.

[0065] According to an embodiment of the present invention, in step (S3), leveling and gelation are carried out at a temperature of less than 60°C.

[0066] According to an embodiment of the present invention, in step (S3), pre-curing is carried out at 80~100 °C, for example in an oven at 80~100 °C. After pre-curing, the adhesive film is initially formed.

[0067] According to an embodiment of the present invention, in step (S3), removing water-soluble impurities from the adhesive film specifically involves rinsing the pre-cured adhesive film with hot water (60~90℃) to remove water-soluble impurities from the adhesive film.

[0068] According to an embodiment of the present invention, in step (S4), the water-soluble impurity refers to at least one of the coagulant, emulsifier and crosslinking agent remaining in the adhesive film.

[0069] According to an embodiment of the present invention, in step (S4), the conditions for heat setting and curing include: heat setting temperature of 100~150 °C and time of 20~40 min.

[0070] Preferably, the heat setting and curing are carried out in an oven.

[0071] According to an embodiment of the present invention, in step (S4), after heat setting and curing, surface treatment can also be performed. For example, after heat setting and curing, the gloves can be surface treated as needed to improve wearing performance.

[0072] According to an embodiment of the present invention, in step (S4), demolding can be performed in a manner known in the art, such as peeling the finished glove off the hand mold by air blowing or manual means.

[0073] Beneficial effects: This invention successfully combines bio-based polyester with mature industrial production technology to prepare a new generation of protective gloves that are high-performance, environmentally friendly, safe, and hypoallergenic, possessing broad market prospects and significant social value. Specifically: (1) Green sustainability: The core component of the latex gloves of this invention is bio-based polyester, which uses diols and bio-based dicarboxylic acids as raw materials, both of which are derived from renewable biomass resources. This eliminates the dependence on petroleum resources from the source, reduces the carbon footprint of the product, and meets the requirements of green chemistry and sustainable development.

[0074] (2) The core component of the latex gloves of the present invention, bio-based polyester, has excellent comprehensive performance: through carefully designed monomer formulation, especially the innovative introduction of molecular structure regulators, a polyester elastomer with a slightly branched / crosslinked network structure is constructed, which makes the final glove product have a tensile strength ≥3 MPa and an elongation at break ≥300%.

[0075] (3) The latex gloves of the present invention have low allergenicity and high biocompatibility: The latex gloves of the present invention do not contain natural latex protein, which fundamentally avoids type I latex allergy and provides a safer choice for people with allergies.

[0076] (4) Potential biodegradability: In the latex gloves of the present invention, the ester bonds in the bio-based polyester structure can be hydrolyzed by microorganisms in the natural environment (such as soil and compost), causing the material to degrade into carbon dioxide and water, which is environmentally friendly. Compared with almost non-degradable nitrile rubber and PVC materials, the gloves of the present invention provide a feasible solution to the problem of single-use plastic waste pollution.

[0077] (5) Process compatibility and economy: The latex glove preparation method of the present invention is applicable to existing mature latex glove impregnation production lines, without the need for large-scale modification of core equipment, and has good industrial feasibility. Attached Figure Description

[0078] Figure 1 The infrared spectrum of the bio-based polyester prepared in Example 1 is shown.

[0079] Figure 2 The bio-based polyester of Example 1 1 H-NMR spectrum.

[0080] Figure 3 For the polyester of Comparative Example 1 1 H-NMR spectrum.

[0081] Figure 4 The image shows the DSC curve of the bio-based polyester from Example 1. Detailed Implementation

[0082] Polyester A polyester comprising the structural unit shown in formula (I): (I) U1, U2, U3, and U4 may be the same or different, and are independently selected from C1, U2, U3, and U4, which are chemically bonded, unsubstituted, or substituted by at least one group represented by formula (A). 1-10 alkylene, unsubstituted, or substituted with at least one group of formula (A) 2-10 alkenyl; (A) Each Q may be the same or different, and each is independently selected from chemical bonds or C. 1-10 Alkylene; Each R m They are the same or different, and are selected independently from H or C. 1-10 alkyl; Each R n They are the same or different, and are selected independently from H or C. 1-10 alkyl; Z1, Z2, Z3, and Z4 may be the same or different, and are independently selected from chemical bonds or C bonds. 1-10 Alkylene; Represents chemical bonds; 'a' represents a number from 6 to 30; b represents a number between 8 and 35; c represents a number from 16 to 65; d represents a number from 0 to 5; The condition is that two, three, or four of U1, U2, U3, and U4 are selected from C1, U2, U3, and U4 that are unsubstituted or substituted by at least one group represented by formula (A). 2-10 It is an alkenyl group, and at most one of U1, U2, U3 and U4 is a chemical bond.

[0083] According to an embodiment of the present invention, the structural unit shown in formula (I) has the structure shown in formula (II): (II) Among them, Y1, Y2, Y6, Y7, Y8, and Y9 are the same or different, and are independently selected from C. 1-10 Alkylene; Y3, Y4, and Y9 may be the same or different, and are independently selected from chemical bonds, C... 1-10 Alkylene or C 2-10 alkenyl; Y5 is selected from C 1-10 Mesenchymal or carbon atom; Y6 is selected from C 1-10 Alkylene or C 1-10 Phenyl group; Indicates a single or double bond, provided that when When representing a single bond, Y5 is C. 1-10 Phenylene group, Y6 is C 1-10 alkylene; when When representing a double bond, Y5 represents a carbon atom and Y6 represents a carbon atom. 1-10 Phenyl group; Z1, Z2, Z3, and Z4 may be the same or different, and are independently selected from chemical bonds or C bonds. 1-10 Alkylene; R1, R2, R3, and R4 may be the same or different, and are independently selected from H or C. 1-10 alkyl; Q1 is selected from chemical bonds or C. 1-10 Alkylene; Each R a They are the same or different, and are selected independently from H or C. 1-10 alkyl; Each R b They are the same or different, and are selected independently from H or C. 1-10 alkyl; R5 and R6 may be the same or different, and are independently selected from H and C. 1-10 Alkyl groups or groups represented by formula (B): (B) Q2 is selected from chemical bonds or C. 1-10 Alkylene; Each R cThey are the same or different, and are selected independently from H or C. 1-10 alkyl; Each R d They are the same or different, and are selected independently from H or C. 1-10 alkyl; Represents chemical bonds; 'a' represents a number from 6 to 30; b represents a number between 8 and 35; c represents a number from 16 to 65; d represents a number from 0 to 5.

[0084] According to an embodiment of the present invention, 'a' represents a number from 6 to 30, such as 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30.

[0085] b represents a number from 8 to 35, such as 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35.

[0086] c represents a number from 16 to 65, for example, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65.

[0087] d represents a number from 0 to 5, such as 0, 1, 2, 3, 4, 5.

[0088] As an example, the structural unit shown in equation (I) is selected from at least one of the following structural units (i), (ii) and (iii): (i) Where a represents a number from 15 to 30, b represents a number from 20 to 35, and c represents a number from 40 to 65; (ii) Where a represents a number from 12 to 24, b represents a number from 16 to 28, c represents a number from 32 to 52, and d represents a number from 0 to 5; (iii) wherein, a represents a number of 6 to 12, b represents a number of 8 to 14, and c represents a number of 16 to 26.

[0089] According to an embodiment of the present invention, the polyester further comprises a structural unit represented by the following formula (III): (III) wherein, Alk1, Alk2, Alk3 are the same or different, and are each independently selected from C 1-12 alkylene group.

[0090] Preferably, the polyester comprises the structural unit represented by formula (D) and the structural unit represented by formula (E): (D) (E) wherein, D1, D2, D3, E1, E2, E3 are the same or different, and are each independently selected from C 1-12 alkylene group; with the proviso that one, two or three of the following conditions are satisfied: (1) D1 is different from E1; (2) D2 is different from E2; (3) D3 is different from E3.

[0091] As an example, the number of carbon atoms in D1 < the number of carbon atoms in E1, for example, D1 is selected from C 1-3 alkyl group, E1 is selected from C 4-10 alkyl group; and / or, the number of carbon atoms in D3 < the number of carbon atoms in E3, for example, D3 is selected from C 1-3 alkyl group, E3 is selected from C 4-10 alkyl group.

[0092] As an example, the number of carbon atoms in D1 > the number of carbon atoms in E1, for example, D1 is selected from C 4-10 alkyl group, E1 is selected from C 1-3 alkyl group; and / or, the number of carbon atoms in D3 > the number of carbon atoms in E3, for example, D3 is selected from C 4-10 alkyl group, E3 is selected from C 1-3 alkyl group.

[0093] As an example, the number of carbon atoms in D2 < the number of carbon atoms in E2, for example, D2 is selected from C 1-6 alkyl group, E2 is selected from C 7-12 alkyl group.

[0094] As an example, the number of carbon atoms in D2 > the number of carbon atoms in E2, for example, D2 is selected from C 7-12 alkyl group, E2 is selected from C 1-6 alkyl group.

[0095] According to an embodiment of the present invention, the polyester is obtained by a reaction between a saturated diol, a saturated diacid, and a molecular structure modifier; wherein the molecular structure modifier is selected from a double-terminated hydroxyl telechelic polymer containing C=C bonds.

[0096] Preferably, the polyester has structural units represented by formula (I) as described above (such as structural units represented by formula (II), (i), (ii) or (iii); and structural units represented by formula (III) (such as structural units represented by formula (D) and formula (E)).

[0097] According to an embodiment of the present invention, the reaction between the saturated diol, the saturated diacid, and the molecular structure modifier is an esterification reaction and a polycondensation reaction.

[0098] According to an embodiment of the present invention, the C=C bond-containing dual-hydroxyl telechelic polymer is selected from one of dual-hydroxyl polybutadiene (HTPB), dual-hydroxyl polyisoprene, and dual-hydroxyl myrcene, preferably dual-hydroxyl polybutadiene.

[0099] According to embodiments of the present invention, the hydroxyl values ​​of the C=C-terminated hydroxyl telechelic polymers are the same or different, and are independently selected from 0.1-1 mmol / g, for example 0.47-0.53 mmol / g, 0.54-0.64 mmol / g, 0.65-0.70 mmol / g or 0.71-0.80 mmol / g.

[0100] According to an embodiment of the present invention, the saturated diol is selected from at least two of ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol, preferably 1,2-propanediol and 1,4-butanediol.

[0101] According to an embodiment of the present invention, the saturated dicarboxylic acid is selected from at least two of succinic acid, glutaric acid, adipic acid, and sebacic acid, preferably 1,6-adipic acid and 1,10-sebacic acid.

[0102] According to an embodiment of the present invention, the molar ratio of the total molar amount of -OH in the saturated diol and the C=C-terminated hydroxyl telechelic polymer to the molar amount of -COOH in the saturated dicarboxylic acid is (1.05~1.8):1, preferably (1.1~1.4):1, for example 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1.

[0103] According to an embodiment of the present invention, the amount of -OH in the C=C-containing double-terminated hydroxyl telechelic polymer is 0.1% to 1.0% of the total molar amount of -OH in the saturated diol and the C=C-containing double-terminated hydroxyl telechelic polymer, preferably 0.15% to 0.50%, for example 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%.

[0104] According to an embodiment of the present invention, the C=C double bond content in the polyester is 1.0 mol% to 15.0 mol%, preferably 2.0 mol% to 15.0 mol%, more preferably 6 mol% to 15.0 mol%. For example, the C=C double bond content in the polyester is 1.0 mol%, 1.5 mol%, 1.6 mol%, 1.7 mol%, 1.8 mol%, 1.9 mol%, 2.0 mol%, 2.1 mol%, 2.2 mol%, 2.3 mol%, 2.4 mol%, 2.5 mol%, 2.6 mol%, 2.7 mol%, 2.8 mol%, 2.9 mol%, 3.0 mol%, 3.5 mol%, 4.0 mol%, 4.5 mol%, 5.0 mol%, 5.5 mol%, 6.0 mol%, 6.5 mol%, 7.0 mol%, 7.5 mol%, 8.0 mol%, 8.5 mol%, 9.0 mol%, 9.5 mol%, 10.0 mol%, 10.5 mol%, 11.0 mol%, 11.5 mol%, 12.0 mol%, 12.5 mol%, 13.0 mol%, 13.5 mol%. mol%, 14.0 mol%, 14.5 mol%, 15.0 mol%.

[0105] According to an embodiment of the present invention, an antioxidant and a polymerization inhibitor are also added during the esterification reaction.

[0106] According to an embodiment of the present invention, the antioxidant is selected from one or two of antioxidant 1010, antioxidant 245, phosphoric acid, phosphorous acid, and phosphate ester.

[0107] According to an embodiment of the present invention, the amount of antioxidant used is 0.01% to 0.6% of the total mass of diol and diacid, preferably 0.01% to 0.2%.

[0108] According to an embodiment of the present invention, the polymerization inhibitor is selected from at least one of hydroquinone, benzoquinone, tetrachlorobenzoquinone, 1,3,5-trinitrobenzene, and 1,1-diphenyl-2-trinitrobenzylhydrazine.

[0109] According to an embodiment of the present invention, the amount of the polymerization inhibitor is 0.01% to 0.6% of the total mass of the diol and diacid, preferably 0.01% to 0.2%.

[0110] According to an embodiment of the present invention, a catalyst is also added during the polycondensation reaction.

[0111] According to an embodiment of the present invention, the catalyst is selected from titanium-based catalysts, antimony-based catalysts, and tin-based catalysts, such as at least one of tetrabutyl titanate, tetraisopropyl titanate, antimony trioxide, stannous octoate, and stannous chloride.

[0112] According to an embodiment of the present invention, the amount of catalyst used is 0.05% to 1.5% of the total mass of the diol and diacid, preferably 0.1% to 0.5%, for example 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%.

[0113] According to an embodiment of the present invention, the number average molecular weight of the polyester is greater than 15,000, for example, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000 or a range between any two of the above values.

[0114] According to an embodiment of the present invention, the polydispersity index of the polyester is less than 5, for example, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.5, 3.0, or 4.0.

[0115] According to an embodiment of the present invention, the glass transition temperature of the polyester is -25°C to -60°C, for example -26°C, -30°C, -35°C, -40°C, -45°C, -50°C, -54°C, and -58°C.

[0116] According to an embodiment of the present invention, the polyester is a bio-based polyester, which is prepared using at least one bio-based source raw material. Preferably, one, two, or all of the saturated diol, saturated diacid, and molecular structure modifier are bio-based.

[0117] According to an embodiment of the present invention, the polyester is an elastomer, preferably a bio-based polyester elastomer.

[0118] Preparation methods of polyester The above-mentioned method for preparing polyester includes reacting saturated diol, saturated diacid and molecular structure modifier.

[0119] According to an embodiment of the present invention, the reaction between the saturated diol, the saturated diacid, and the molecular structure modifier is an esterification reaction and a polycondensation reaction.

[0120] According to an embodiment of the present invention, the preparation method includes the following steps: (A1) Saturated diol, saturated diacid, molecular structure modifier, antioxidant, and polymerization inhibitor are mixed and esterified in an inert atmosphere. (A2) After the esterification reaction is completed, a catalyst is added under an inert atmosphere, the temperature is raised to the temperature of the polycondensation reaction, and the polycondensation reaction is carried out under vacuum to obtain the polyester.

[0121] According to embodiments of the present invention, the saturated diol, saturated dicarboxylic acid, molecular structure modifier, antioxidant, polymerization inhibitor, and catalyst described above have the meanings as stated above.

[0122] According to an embodiment of the present invention, in step (A1), the esterification reaction is carried out under normal pressure.

[0123] According to an embodiment of the present invention, in step (A1), the inert atmosphere refers to an atmosphere that is inert to the reaction, such as N2.

[0124] According to an embodiment of the present invention, in step (A1), the temperature of the esterification reaction is 160~200℃, preferably 170~190℃; the time of the esterification reaction is 2~4h, preferably 2.5~3.5h.

[0125] According to an embodiment of the present invention, in step (A2), the temperature of the polycondensation reaction is 200~240℃, preferably 210~230℃; the time of the polycondensation reaction is 2~10h, preferably 3~8h.

[0126] According to an embodiment of the present invention, in step (A2), the polycondensation reaction is carried out under a vacuum. A vacuum state known in the art can be selected, such as a pressure below 800 Pa, preferably below 500 Pa.

[0127] According to an embodiment of the present invention, in step (A2), during the polycondensation reaction, small molecules and water are removed from the system.

[0128] According to an embodiment of the present invention, in step (A2), after the polycondensation reaction is completed, the polyester is collected, and a method known in the art can be used for collection; for example, an inert gas is introduced to expel the polyester from the reaction apparatus.

[0129] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.

[0130] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0131] Performance testing methods in the following examples Mechanical performance testing: The tensile strength and elongation at break of the gloves were tested using an electronic universal tensile testing machine in accordance with the GB_T 7543-2020 standard.

[0132] Example 1 (1) Synthesis of bio-based polyester elastomer: In a reaction apparatus equipped with a mechanical stirrer, nitrogen inlet and outlet, heating device, thermometer and condenser, 0.41 mol of 1,2-propanediol, 0.41 mol of 1,4-butanediol, 0.32 mol of sebacic acid, 0.36 mol of succinic acid, approximately 0.00137 mol of hydroxyl-terminated polybutadiene, and 0.1 wt% of antioxidant 1010 and 0.01 wt% of hydroquinone were added sequentially; stirring was started and nitrogen was introduced for 30 min to purge the air from the apparatus; under nitrogen atmosphere protection, the temperature was raised to 180℃ and esterification reaction was carried out for 4 h; after the reaction was completed, 0.2 wt% of tetrabutyl titanate was added, and then the pressure was gradually reduced to below 800 Pa while the temperature was slowly raised to 220℃ to carry out polycondensation reaction for 5 h. h; After the reaction is complete, heating is stopped, nitrogen gas is introduced to restore normal pressure, and the material is discharged while hot to obtain a light yellow transparent viscous bio-based polyester with Mn of 40214, Mw of 75602, PDI of 1.88, double bond content of 3.49 mol%, and Tg of -58.89℃. (2) Preparation of bio-based polyester latex: 7.5 g of the bio-based polyester elastomer prepared by the above method was dissolved in 30 g of dichloromethane to prepare a polymer solution with a mass fraction of 20%; 37.5 g of deionized water, 0.15 g of sodium dodecylbenzenesulfonate and 0.075 g of dicumyl peroxide were added to a container equipped with a high-speed dispersion homogenizer to prepare an emulsifier aqueous dispersion; the obtained polymer solution was slowly added dropwise to the above emulsifier aqueous dispersion under high-speed stirring to pre-emulsify and obtain a primary emulsion; the pre-emulsified primary emulsion was passed through a high-pressure homogenizer and circulated 3 times under a pressure of 50 MPa to form a stable and uniform emulsion; the homogenized emulsion was subjected to 40°C and reduced pressure to remove organic solvent; after solvent removal, the pH value of the emulsion was adjusted to 8.0; finally, the solid content of the emulsion was adjusted to 30% as needed to obtain the final bio-based polyester latex. (3) Preparation of bio-based polyester latex gloves: The ceramic hand mold was acid-washed, alkali-washed and water-washed in sequence to remove surface dirt, and then dried in an oven at 80°C for later use; the clean and dry hand mold was immersed in a calcium nitrate solution at 50°C with a mass fraction of 10%, left for a few seconds and then slowly removed, and then dried in an oven at 70°C to dry the thin layer of calcium nitrate on the surface of the hand mold; the hand mold with calcium nitrate coating was steadily immersed in a bio-based polyester latex tank that had been prepared and maintained at 20°C for 5 seconds; the hand mold with wet gel film was slowly removed from the latex tank, leveled and gelled at room temperature, and then pre-cured in an oven at 80°C to allow the film to initially form; the pre-cured gloves were placed in a hot water rinsing tank (60°C) to remove residual calcium nitrate, emulsifier and other water-soluble impurities in the film by water rinsing; the rinsed gloves were sent to the main oven for final heat setting and curing; the heat setting temperature was 100°C and the time was 40 seconds. min; after curing, the finished gloves are peeled off the hand mold manually; after testing, its tensile strength is 4 MPa, its elongation at break is 600%, and it is biodegradable.

[0133] Example 2 (1) Synthesis of bio-based polyester elastomer: In a reaction apparatus equipped with a mechanical stirrer, nitrogen inlet and outlet, heating device, thermometer and condenser, 0.356 mol of ethylene glycol, 0.178 mol of 1,3-propanediol, 0.178 mol of 1,4-butanediol, 0.32 mol of glutaric acid, 0.36 mol of succinic acid, approximately 0.0014 mol of hydroxyl-terminated polyisoprene and 0.1 wt% of antioxidant 245 and 0.05 wt% of benzoquinone were added sequentially; stirring was started and nitrogen was introduced for 30 min to purge the air from the apparatus; under nitrogen atmosphere protection, the temperature was raised to 190℃ and esterification reaction was carried out for 5 h; after the reaction was completed, 0.5 wt% of tetraisopropyl titanate was added, and then the pressure was gradually reduced to below 800 Pa while the temperature was slowly raised to 230℃ to carry out polycondensation reaction 2 h. h; After the reaction is complete, heating is stopped, nitrogen gas is introduced to restore normal pressure, and the material is discharged while hot to obtain a light yellow transparent viscous bio-based polyester with Mn of 12043, Mw of 25488, PDI of 1.95, double bond content of 0.98 mol%, and Tg of -18.06℃. (2) Preparation of bio-based polyester latex: 7.5 g of the bio-based polyester elastomer prepared by the above method was dissolved in 37.5 g of chloroform to prepare a polymer solution with a mass fraction of 20%; 37.5 g of deionized water, 0.225 g of sodium dodecyl sulfate and 0.075 g of 2,4-di-tert-butyl peroxide were added to a container equipped with a high-speed dispersion homogenizer to prepare an emulsifier aqueous dispersion; the obtained polymer solution was slowly added dropwise to the above emulsifier aqueous dispersion under high-speed stirring to pre-emulsify and obtain a primary emulsion; the pre-emulsified primary emulsion was passed through a high-pressure homogenizer and circulated twice under a pressure of 60 MPa to form a stable and uniform emulsion; the homogenized emulsion was subjected to 45°C and reduced pressure to remove organic solvent; after solvent removal, the pH of the emulsion was adjusted to 8.5; finally, the solid content of the emulsion was adjusted to 35% as needed to obtain the final bio-based polyester latex. (3) Preparation of bio-based polyester latex gloves: The ceramic hand mold was acid-washed, alkali-washed and water-washed in sequence to remove surface dirt, and then dried in an oven at 85°C for later use; the clean and dry hand mold was immersed in a calcium chloride solution at 55°C with a mass fraction of 15%, and after a few seconds it was slowly removed, and then the calcium chloride thin layer on the surface of the hand mold was dried in an oven at 75°C; the hand mold with calcium chloride coating was steadily immersed in a bio-based polyester latex tank that had been prepared and maintained at 25°C for 10 seconds; the hand mold with wet gel film was slowly removed from the latex tank, leveled and gelled at room temperature, and then pre-cured in an oven at 85°C to allow the film to initially form; the pre-cured gloves were placed in a hot water rinsing tank (65°C) to remove water-soluble impurities such as residual calcium chloride and emulsifier from the film; the rinsed gloves were sent to the main oven for final heat setting and curing; the heat setting temperature was 110°C and the time was 25 seconds. min; after curing, the finished gloves are peeled off the hand mold manually; after testing, its tensile strength is 3 MPa, its elongation at break is 300%, and it is biodegradable.

[0134] Example 3 (1) Synthesis of bio-based polyester elastomer: In a reaction apparatus equipped with a mechanical stirrer, nitrogen inlet and outlet, heating device, thermometer and condenser, 0.4 mol of 1,5-pentanediol, 0.4 mol of 1,6-hexanediol, 0.18 mol of adipic acid, 0.18 mol of succinic acid, 0.37 mol of sebacic acid, approximately 0.004 mol of hydroxyl-terminated polybutadiene-acrylonitrile rubber, 0.004 mol of hydroxyl-terminated polyisoprene, and 0.1 wt% of phosphoric acid and 0.1 wt% of tetrachlorobenzoquinone by total monomer mass were added sequentially; stirring was started, and nitrogen was introduced for 30 min to purge the air in the apparatus; under nitrogen atmosphere protection, the temperature was raised to 160℃ for esterification reaction for 6 h; after the reaction was completed, 0.05 wt% of antimony trioxide by total monomer mass was added, and then the pressure was gradually reduced to below 800 Pa, while the temperature was slowly raised to 170℃ for polycondensation reaction for 10 h. h; After the reaction is complete, heating is stopped, nitrogen gas is introduced to restore normal pressure, and the material is discharged while hot to obtain a light yellow transparent viscous bio-based polyester with Mn of 11697, Mw of 27687, PDI of 2.37, double bond content of 1.9 mol%, and Tg of -39.46℃. (2) Preparation of bio-based polyester latex: 7.5 g of the bio-based polyester elastomer prepared by the above method was dissolved in 30 g of dichloromethane to prepare a polymer solution with a mass fraction of 20%; 37.5 g of deionized water, 0.3 g of sodium dodecylbenzenesulfonate and 0.15 g of dicumyl peroxide were added to a container equipped with a high-speed dispersion homogenizer to prepare an emulsifier aqueous dispersion; the obtained polymer solution was slowly added dropwise to the above emulsifier aqueous dispersion under high-speed stirring to pre-emulsify and obtain a primary emulsion; the pre-emulsified primary emulsion was passed through a high-pressure homogenizer and circulated twice under a pressure of 70 MPa to form a stable and uniform emulsion; the homogenized emulsion was subjected to 50°C and reduced pressure to remove organic solvent; after solvent removal, the pH value of the emulsion was adjusted to 9.0; finally, the solid content of the emulsion was adjusted to 40% as needed to obtain the final bio-based polyester latex. (3) Preparation of bio-based polyester latex gloves: The ceramic hand mold was acid-washed, alkali-washed and water-washed in sequence to remove surface dirt, and then dried in an oven at 90°C for later use; the clean and dry hand mold was immersed in a calcium chloride solution at 60°C with a mass fraction of 20%, and slowly removed after a few seconds, and then dried in an oven at 80°C to dry the thin layer of calcium chloride on the surface of the hand mold; the hand mold with calcium chloride coating was steadily immersed in a bio-based polyester latex tank that had been prepared and maintained at 30°C for 15 seconds; the hand mold with wet gel film was slowly removed from the latex tank, leveled and gelled at room temperature, and then pre-cured in an oven at 90°C to allow the film to initially form; the pre-cured gloves were placed in a hot water rinsing tank (70°C) to remove water-soluble impurities such as residual calcium chloride and emulsifier from the film by water rinsing; the rinsed gloves were sent to the main oven for final heat setting and curing; the heat setting temperature was 120°C and the time was 30 seconds. min; after curing, the finished gloves are peeled off the hand mold manually; after testing, its tensile strength is 10 MPa, its elongation at break is 800%, and it is biodegradable.

[0135] Example 4 (1) Synthesis of bio-based polyester elastomer: In a reaction apparatus equipped with a mechanical stirrer, nitrogen inlet and outlet, heating device, thermometer and condenser, 0.61 mol of 1,2-propanediol, 0.61 mol of 1,4-butanediol, 0.32 mol of adipic acid, 0.36 mol of sebacic acid, about 0.01 mol of dihydroxymyrcene, and 0.1 wt% of antioxidant 1010 and 0.6 wt% of hydroquinone were added sequentially; stirring was started and nitrogen was introduced for 30 min to purge the air in the apparatus; under nitrogen atmosphere protection, the temperature was raised to 200℃ and esterification reaction was carried out for 2 h; after the reaction was completed, 1.0 wt% of tetrabutyl titanate and 0.5 wt% of tetraisopropyl titanate were added, and then the pressure was gradually reduced to below 800 Pa, while the temperature was slowly raised to 200℃ to carry out polycondensation reaction for 4 h. h; After the reaction is complete, heating is stopped, nitrogen gas is introduced to restore normal pressure, and the material is discharged while hot to obtain a light yellow transparent viscous bio-based polyester with Mn of 19756, Mw of 42653, PDI of 2.16, double bond content of 3.2 mol%, and Tg of -34.26℃. (2) Preparation of bio-based polyester latex: Take 7.5 g of the bio-based polyester elastomer prepared by the above method and dissolve it in 37.5 g of... A polymer solution with a mass fraction of 16.7% was prepared in tetrahydrofuran. In a container equipped with a high-speed homogenizer, 37.5 g of deionized water, 0.105 g of sodium dodecylbenzenesulfonate, 0.12 g of sodium dodecyl sulfate, and 0.15 g of dicumyl peroxide were added to prepare an emulsifier aqueous dispersion. The obtained polymer solution was slowly added dropwise to the emulsifier aqueous dispersion under high-speed stirring to pre-emulsify and obtain a primary emulsion. The pre-emulsified primary emulsion was passed through a high-pressure homogenizer and circulated twice at 80 MPa to form a stable and homogeneous emulsion. The homogenized emulsion was then subjected to 55°C and reduced pressure to remove the organic solvent. After solvent removal, the pH of the emulsion was adjusted to 9.5. Finally, the solid content of the emulsion was adjusted to 45% as needed to obtain the final bio-based polyester latex. (3) Preparation of bio-based polyester latex gloves: The ceramic hand mold was acid-washed, alkali-washed and water-washed in sequence to remove surface dirt, and then dried in an oven at 95°C for later use; the clean and dry hand mold was immersed in a calcium nitrate solution at 65°C and 25% by mass, left for a few seconds and then slowly removed, and then dried in an oven at 85°C to dry the thin layer of calcium nitrate on the surface of the hand mold; the hand mold with calcium nitrate coating was steadily immersed in a bio-based polyester latex tank that had been prepared and maintained at 25°C for 20 seconds; the hand mold with wet gel film was slowly removed from the latex tank, leveled and gelled at room temperature, and then pre-cured in an oven at 95°C to allow the film to initially form; the pre-cured gloves were placed in a hot water rinsing tank (75°C) to remove residual calcium nitrate, emulsifier and other water-soluble impurities in the film by water rinsing; the rinsed gloves were sent to the main oven for final heat setting and curing; the heat setting temperature was 130°C and the time was 35 seconds. min; after curing, the finished gloves are peeled off the hand mold manually; after testing, its tensile strength is 15 MPa, its elongation at break is 700%, and it is biodegradable.

[0136] Example 5 (1) Synthesis of bio-based polyester elastomer: In a reaction apparatus equipped with a mechanical stirrer, nitrogen inlet and outlet, heating device, thermometer and condenser, 0.47 mol of 1,2-propanediol, 0.47 mol of 1,4-butanediol, 0.36 mol of adipic acid, 0.32 mol of sebacic acid, approximately 0.0047 mol of hydroxyl-terminated polybutadiene, and 0.1 wt% of antioxidant 245 and 0.2 wt% of 1,3,5-trinitrobenzene were added sequentially; stirring was started and nitrogen was introduced for 30 min to purge the air from the apparatus; under nitrogen atmosphere protection, the temperature was raised to 170 °C and the esterification reaction was carried out for 4.5 h; after the reaction was completed, 1.0 wt% of tetraisopropyl titanate was added, and then the pressure was gradually reduced to 800 °C. The pressure was kept below Pa, and the temperature was slowly raised to 210℃ for 3 hours to carry out the polycondensation reaction. After the reaction was completed, heating was stopped, nitrogen was introduced to restore normal pressure, and the material was discharged while hot to obtain a light yellow transparent viscous bio-based polyester with Mn of 16589, Mw of 34165, PDI of 2.06, double bond content of 2.2 mol%, and Tg of -28.28℃. (2) Preparation of bio-based polyester latex: 7.5 g of the bio-based polyester elastomer prepared by the above method was dissolved in 33.75 g of dichloromethane to prepare a polymer solution with a mass fraction of 18%; 37.5 g of deionized water, 0.15 g of polyethylene glycol octylphenyl ether, 0.15 g of dicumyl peroxide and 0.15 g of 2,4-di-tert-butyl peroxide were added to a container equipped with a high-speed dispersion homogenizer to prepare an emulsifier aqueous dispersion; the obtained polymer solution was slowly added dropwise to the above emulsifier aqueous dispersion under high-speed stirring to pre-emulsify and obtain a primary emulsion; the pre-emulsified primary emulsion was passed through a high-pressure homogenizer at 90°C. The emulsion was circulated twice under pressure of MPa to form a stable and uniform emulsion. The homogenized emulsion was then subjected to 60°C and reduced pressure to remove the organic solvent. After solvent removal, the pH of the emulsion was adjusted to 10. Finally, the solid content of the emulsion was adjusted to 50% as needed to obtain the final bio-based polyester latex. (3) Preparation of bio-based polyester latex gloves: The ceramic hand mold was acid-washed, alkali-washed and water-washed in sequence to remove surface dirt, and then dried in an oven at 100°C for later use; the clean and dry hand mold was immersed in a calcium nitrate solution at 70°C and 30% by mass, left for a few seconds and then slowly removed, and then dried in an oven at 90°C to dry the thin layer of calcium nitrate on the surface of the hand mold; the hand mold with calcium nitrate coating was steadily immersed in a bio-based polyester latex tank that had been prepared and maintained at 25°C for 10 seconds; the hand mold with wet gel film was slowly removed from the latex tank, leveled and gelled at room temperature, and then pre-cured in an oven at 100°C to allow the film to initially form; the pre-cured gloves were placed in a hot water rinsing tank (80°C) to remove residual calcium nitrate, emulsifier and other water-soluble impurities in the film by water rinsing; the rinsed gloves were sent to the main oven for final heat setting and curing; the heat setting temperature was 140°C and the time was 25 seconds. min; after curing, the finished gloves are peeled off the hand mold manually; after testing, its tensile strength is 12 MPa, its elongation at break is 750%, and it is biodegradable.

[0137] Example 6 (1) Synthesis of bio-based polyester elastomer: In a reaction apparatus equipped with a mechanical stirrer, nitrogen inlet and outlet, heating device, thermometer and condenser, 0.44 mol of 1,2-propanediol, 0.44 mol of 1,4-butanediol, 0.36 mol of adipic acid, 0.32 mol of sebacic acid, approximately 0.0035 mol of hydroxyl-terminated polybutadiene, and 0.1 wt% of antioxidant 245 and 0.2 wt% of 1,3,5-trinitrobenzene were added sequentially; stirring was started and nitrogen was introduced for 30 min to purge the air from the apparatus; under nitrogen atmosphere protection, the temperature was raised to 180 °C and the esterification reaction was carried out for 5.5 h; after the reaction was completed, 0.1 wt% of tetrabutyl titanate was added, and then the pressure was gradually reduced to 800 °C. The pressure was kept below Pa, and the temperature was slowly raised to 200℃ for 8 hours to carry out the polycondensation reaction. After the reaction was completed, heating was stopped, nitrogen was introduced to restore normal pressure, and the material was discharged while hot to obtain a light yellow transparent viscous bio-based polyester with Mn of 17086, Mw of 36861, PDI of 2.16, double bond content of 2.97 mol%, and Tg of -26.44℃. (2) Preparation of bio-based polyester latex: 7.5 g of the bio-based polyester elastomer prepared by the above method was dissolved in dichloromethane to prepare a polymer solution with a mass fraction of 18%; 37.5 g of deionized water, 0.45 g of polyethylene glycol octylphenyl ether and 0.45 g of dicumyl peroxide were added to a container equipped with a high-speed dispersion homogenizer to prepare an emulsifier aqueous dispersion; the obtained polymer solution was slowly added dropwise to the above emulsifier aqueous dispersion under high-speed stirring to pre-emulsify and obtain a primary emulsion; the pre-emulsified primary emulsion was circulated once under a pressure of 100 MPa by a high-pressure homogenizer to form a stable and uniform emulsion; the homogenized emulsion was subjected to 60°C and reduced pressure to remove organic solvent; after solvent removal, the pH value of the emulsion was adjusted to 8.0; finally, the solid content of the emulsion was adjusted to 50% as needed to obtain the final bio-based polyester latex. (3) Preparation of bio-based polyester latex gloves: The ceramic hand mold was acid-washed, alkali-washed and water-washed in sequence to remove surface dirt, and then dried in an oven at 120°C for later use; the clean and dry hand mold was immersed in a calcium nitrate solution at 60°C and 30% by mass, left for a few seconds and then slowly removed, and then dried in an oven at 70°C to dry the thin layer of calcium nitrate on the surface of the hand mold; the hand mold with calcium nitrate coating was steadily immersed in a bio-based polyester latex tank that had been prepared and maintained at 25°C for 10 seconds; the hand mold with wet gel film was slowly removed from the latex tank, leveled and gelled at room temperature, and then pre-cured in an oven at 100°C to allow the film to initially form; the pre-cured gloves were placed in a hot water rinsing tank (90°C) to remove residual calcium nitrate, emulsifier and other water-soluble impurities in the film by water rinsing; the rinsed gloves were sent to the main oven for final heat setting and curing; the heat setting temperature was 150°C and the time was 20 seconds. min; after curing, the finished gloves are peeled off the hand mold manually; after testing, its tensile strength is 15 MPa, its elongation at break is 700%, and it is biodegradable.

[0138] Example 7 The only difference from Example 6 is that the amount of -OH in the molecular structure modifier in step 1 is 0.1% of the total molar number of -OH in the bio-based diol and the molecular structure modifier, for comparison; all other steps and parameters are exactly the same as in Example 6. The resulting bio-based polyester has a Mn of 21766, a Mw of 46569, a PDI of 2.14, a double bond content of 1.12 mol%, and a Tg of -24.65℃. The bio-based polyester latex gloves tested have a tensile strength of 13 MPa, an elongation at break of 850%, and are biodegradable.

[0139] Example 8 The only difference from Example 6 is that the amount of dicumyl peroxide added in step 2 is 2% of the polyester mass, for comparison; all other steps and parameters are exactly the same as in Example 6. The resulting bio-based polyester has Mn of 17458, Mw of 38661, PDI of 2.21, double bond content of 3.02 mol%, and Tg of -26.79℃. The bio-based polyester latex gloves tested have a tensile strength of 18 MPa, an elongation at break of 550%, and are biodegradable.

[0140] Comparative Example 1 The only difference from Example 6 is that no molecular structure modifier is added in step 1, and the total molar ratio of diacid and diol remains close for comparison; all other steps and parameters are exactly the same as in Example 6. The resulting bio-based polyester has a Mn of 9824, a Mw of 17854, a PDI of 1.82, a double bond content of 0.12 mol%, and a Tg of -22.58℃. The bio-based polyester latex gloves tested have a tensile strength of 3 MPa, an elongation at break of 100%, and are biodegradable.

[0141] Comparative Example 2 The only difference from Example 6 is that no crosslinking agent was added in step 3 for comparison; all other steps and parameters were exactly the same as in Example 6; ultimately, the resulting bio-based polyester latex could not be used to make latex gloves.

[0142] The performance of the latex gloves prepared in Examples 6-8 and Comparative Examples 1-2 was tested, and the results are shown in Table 1.

[0143] Table 1. Performance comparison of latex gloves obtained from different embodiments

[0144] Comparing Example 6 and Comparative Example 1, the only variable was the addition of a molecular structure modifier (hydroxyl-terminated polybutadiene). As shown in Table 1, the Comparative Example 1 sample without the molecular structure modifier exhibited typical brittle polyester characteristics: low tensile strength (3 MPa) and poor elongation at break (100%). In contrast, Example 6, after introducing a small amount of the molecular structure modifier, showed an increase in elongation at break to 700% and tensile strength to 15 MPa, exhibiting excellent elastomer behavior. This demonstrates that the present invention, by introducing a molecular structure modifier as a flexible soft segment through copolymerization, can effectively improve the toughness and elasticity of the material at the molecular chain level, solving the brittleness problem of traditional bio-based polyesters and proving the decisive role of the creative introduction of a molecular structure modifier in the mechanical strength of bio-based polyester gloves.

[0145] Comparing Examples 6 and 7, when the amount of molecular structure modifier added increased from 0.1 mol% to 0.3 mol%, the elongation at break of the material further increased to 850%, but the tensile strength decreased slightly. This is because the content of dihydroxyl-terminated polybutadiene, as a soft segment, makes the material more flexible and easier to stretch when its content increases, but at the same time, it sacrifices some strength due to the relative decrease in the content of hard segments. This shows that by controlling the amount of molecular structure modifier, the mechanical properties of the material can be easily adjusted to meet different application requirements.

[0146] Comparing Example 6 and Comparative Example 2, the only variable was the addition of a crosslinking agent. As shown in Table 1, without the addition of a crosslinking agent, the resulting bio-based polyester latex could not form a film, thus preventing the production of latex gloves. This is because increasing the amount of DCP improved the crosslinking density, forming a denser and more stable three-dimensional crosslinked network, effectively enhancing the material's strength. This confirms that the strategy of using molecular structure adjustment to pre-embed crosslinking sites and performing peroxide crosslinking is an effective means of improving the overall performance of materials.

[0147] In summary, this invention, through innovative formulation design, successfully produces a high-performance bio-based polyester latex glove with good potential for industrial application.

[0148] The exemplary embodiments of the present invention have been described above. However, the scope of protection of the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A bio-based polyester latex glove, characterized in that, The raw materials for the bio-based polyester latex gloves include emulsifiers, crosslinking agents, and polyester containing structural units as shown in formula (I): (I) U1, U2, U3, and U4 may be the same or different, and are independently selected from C1, U2, U3, and U4 that are chemically bonded, unsubstituted, or substituted by at least one group represented by formula (A). 1-10 alkylene, unsubstituted or substituted with at least one group of formula (A) 2-10 alkenyl; (A) Each Q may be the same or different, and each is independently selected from chemical bonds or C. 1-10 Alkylene; Each R m They are the same or different, and are selected independently from H or C. 1-10 alkyl; Each R n They are the same or different, and are selected independently from H or C. 1-10 alkyl; Z1, Z2, Z3, and Z4 may be the same or different, and are independently selected from chemical bonds or C bonds. 1-10 Alkylene; Represents chemical bonds; 'a' represents a number from 6 to 30; b represents a number between 8 and 35; c represents a number from 16 to 65; d represents a number from 0 to 5; The condition is that two, three, or four of U1, U2, U3, and U4 are selected from C1, U2, U3, and U4 that are unsubstituted or substituted by at least one group represented by formula (A). 2-10 It is an alkenyl group, and at most one of U1, U2, U3 and U4 is a chemical bond.

2. The bio-based polyester latex glove according to claim 1, characterized in that, The emulsifier is selected from one, two or more of sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, and polyethylene glycol octylphenyl ether; The crosslinking agent is selected from at least one of dicumyl peroxide and 2,4-di-tert-butyl peroxide; The weight ratio of the polyester, emulsifier, and crosslinking agent is 10:(0.1~0.5):(0.005~1).

3. The bio-based polyester latex glove according to claim 1, characterized in that, The structural unit shown in equation (I) has the structure shown in equation (II): (II) Among them, Y1, Y2, Y6, Y7, Y8, and Y9 are the same or different, and are independently selected from C. 1-10 Alkylene; Y3, Y4, and Y9 may be the same or different, and are independently selected from chemical bonds, C... 1-10 Alkylene or C 2-10 alkenyl; Y5 is selected from C 1-10 Mesenchymal or carbon atom; Y6 is selected from C 1-10 Alkylene or C 1-10 Phenyl group; Indicates a single or double bond, provided that when When representing a single bond, Y5 is C. 1-10 Phenylene group, Y6 is C 1-10 alkylene; when When representing a double bond, Y5 represents a carbon atom and Y6 represents a carbon atom. 1-10 Phenyl group; Z1, Z2, Z3, and Z4 may be the same or different, and are independently selected from chemical bonds or C bonds. 1-10 Alkylene; R1, R2, R3, and R4 may be the same or different, and are independently selected from H or C. 1-10 alkyl; Q1 is selected from chemical bonds or C. 1-10 Alkylene; Each R a They are the same or different, and are selected independently from H or C. 1-10 alkyl; Each R b They are the same or different, and are selected independently from H or C. 1-10 alkyl; R5 and R6 may be the same or different, and are independently selected from H and C. 1-10 Alkyl groups or groups represented by formula (B): (B) Q2 is selected from chemical bonds or C. 1-10 Alkylene; Each R c They are the same or different, and are selected independently from H or C. 1-10 alkyl; Each R d They are the same or different, and are selected independently from H or C. 1-10 alkyl; Represents chemical bonds; 'a' represents a number from 6 to 30; b represents a number between 8 and 35; c represents a number from 16 to 65; d represents a number from 0 to 5; The polyester further comprises the structural unit shown in formula (III): (III) Among them, Alk1, Alk2, and Alk3 may be the same or different, and are independently selected from C. 1-12 Alkylene; The polyester comprises the structural unit shown in formula (D) and the structural unit shown in formula (E): (D) (E) Among them, D1, D2, D3, E1, E2, and E3 are the same or different, and are independently selected from C. 1-12 Alkylene; The condition is that one, two, or three of the following conditions are met: (1) D1 and E1 are not the same; (2) D2 and E2 are not the same; (3) D3 and E3 are not the same.

4. The bio-based polyester latex glove according to claim 1, characterized in that, The polyester is obtained by the reaction between a saturated diol, a saturated diacid, and a molecular structure modifier; wherein the molecular structure modifier is selected from a double-terminated hydroxyl telechelic polymer containing C=C bonds. The C=C bond-containing double-hydroxyl telechelic polymer is selected from one of double-hydroxyl polybutadiene, double-hydroxyl polyisoprene, and double-hydroxyl myrcene. The hydroxyl values ​​of the C=C terminal hydroxyl telechelic polymers are the same or different, and are independently selected from 0.1-1 mmol / g; The saturated diol is selected from at least two of ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol; The saturated dicarboxylic acid is selected from at least two of succinic acid, glutaric acid, adipic acid, and sebacic acid; The molar ratio of the total molar amount of -OH in the saturated diol and the C=C-terminated hydroxyl telechelic polymer to the molar amount of -COOH in the saturated dicarboxylic acid is (1.05~1.8):1; The amount of -OH in the C=C-terminated hydroxyl telechelic polymer is 0.1% to 1.0% of the total molar amount of -OH in the saturated diol and the C=C-terminated hydroxyl telechelic polymer. The C=C double bond content in the polyester is 0.5 mol% to 15.0 mol%.

5. The bio-based polyester latex glove according to claim 1, characterized in that, The reaction between the saturated diol, the saturated dicarboxylic acid and the molecular structure modifier is an esterification reaction and a polycondensation reaction. Antioxidants and polymerization inhibitors are also added during the esterification reaction; The antioxidant is selected from one or two of antioxidant 1010, antioxidant 245, phosphoric acid, phosphorous acid, and phosphate esters; the amount of the antioxidant is 0.01% to 0.6% of the total mass of the diol and diacid; The polymerization inhibitor is selected from at least one of hydroquinone, benzoquinone, tetrachlorobenzoquinone, 1,3,5-trinitrobenzene, and 1,1-diphenyl-2-trinitrobenzylhydrazine; the amount of the polymerization inhibitor is 0.01% to 0.6% of the total mass of the diol and diacid; During the polycondensation reaction, a catalyst is also added; the catalyst is selected from titanium-based catalysts, antimony-based catalysts, and tin-based catalysts; the amount of the catalyst is 0.05% to 1.5% of the total mass of the diol and diacid.

6. The bio-based polyester latex glove according to claim 1, characterized in that, The number-average molecular weight of the polyester is not less than 10,000; The weight-average molecular weight of the polyester is not less than 20,000; The polydispersity index of the polyester is less than 5; The glass transition temperature of the polyester is -25℃ to -60℃; The polyester is a bio-based polyester, which is prepared using at least one bio-based raw material; one, two, or all of the saturated diol, saturated dicarboxylic acid, and molecular structure modifier are bio-based.

7. The method for preparing the bio-based polyester latex gloves according to any one of claims 1-6, characterized in that, The preparation method specifically includes the following steps: (S1) Preparation of bio-based polyester latex: Polyester is dissolved in an organic solvent to prepare a polymer solution with a mass fraction of 15%~40%; emulsifier, crosslinking agent and water are added to the polymer solution for pre-emulsification treatment, followed by homogenization treatment, and then the organic solvent is removed to obtain bio-based polyester latex. (S2) Hand mold impregnation with coagulant: Immerse the hand mold in a coagulant solution with a temperature of 50~70℃ and a mass fraction of 10%~30%, leave it for a few seconds, then slowly remove it and dry it in an oven at 70~90℃ to form a coagulant coating on the surface of the hand mold. (S3) Impregnating latex: The hand mold with coagulant coating in step (S3) is impregnated in the bio-based polyester latex of step (S2) for 5~20 seconds and then slowly removed. After leveling, gelling and pre-curing, a film is obtained. (S4) After removing water-soluble impurities from the adhesive film, heat setting and curing are performed, and the bio-based polyester latex gloves are obtained by demolding.

8. The preparation method according to claim 7, characterized in that, In step (S1), the polyester is obtained by reacting a saturated diol, a saturated diacid, and a molecular structure modifier. And / or, the method for synthesizing the polyester specifically includes the following steps: (A1) Saturated diol, saturated diacid, molecular structure modifier, antioxidant, and polymerization inhibitor are mixed and esterified in an inert atmosphere. (A2) After the esterification reaction is completed, a catalyst is added under an inert atmosphere, the temperature is raised to the temperature of the polycondensation reaction, and the polycondensation reaction is carried out under vacuum to obtain the polyester. In step (A1), the esterification reaction is carried out under normal pressure conditions; In step (A1), an inert atmosphere refers to an atmosphere that is inert to the reaction; In step (A1), the esterification reaction temperature is 160~200℃; the esterification reaction time is 2~4 h; In step (A2), the temperature of the polycondensation reaction is 200~240℃; the time of the polycondensation reaction is 2~10 h; In step (A2), the polycondensation reaction is carried out under vacuum. In step (A2), during the polycondensation reaction, small molecules and water are removed from the system.

9. The preparation method according to claim 7, characterized in that, In step (S1), the organic solvent is selected from one, two or more of dichloromethane, trichloromethane, and tetrahydrofuran; In step (S1), the emulsifier is selected from one, two or more of sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, and polyethylene glycol octylphenyl ether; In step (S1), the crosslinking agent is selected from at least one of dicumyl peroxide and 2,4-di-tert-butyl peroxide; In step (S1), the weight ratio of polyester to emulsifier is 10:(0.1~0.5); In step (S1), the weight ratio of polyester, organic solvent and water is 10:(30~100):(10~100); In step (S1), the mass ratio of the crosslinking agent to the polyester is 0.005-1:10; In step (S1), the pre-emulsification process specifically includes: preparing an emulsifier aqueous dispersion by mixing water, emulsifier, and crosslinking agent; and adding the polymer solution dropwise to the emulsifier aqueous dispersion under high-speed stirring to perform pre-emulsification and obtain a primary emulsion. In step (S1), the homogenization process specifically includes: passing the pre-emulsified primary emulsion through a high-pressure homogenizer and circulating it 1 to 3 times under a pressure of 50 to 100 MPa to form a stable and uniform emulsion. In step (S1), the removal of organic solvents specifically includes: removing organic solvents from the homogenized emulsion under reduced pressure at 40~60 °C; In step (S1), after removing the organic solvent, a post-treatment is performed; the post-treatment includes adjusting the pH value to 8.0~10.0; In step (S1), water is optionally added to adjust the solid content of the bio-based polyester latex, which is 30% to 50%.

10. The preparation method according to claim 7, characterized in that, The coagulant solution comprises a calcium salt and water; the calcium salt is selected from calcium nitrate or calcium chloride. The impregnation temperature is 20~30℃; In step (S3), leveling and gelation are carried out at temperatures below 60°C. In step (S3), pre-curing is carried out at 80~100 ℃; In step (S3), removing water-soluble impurities from the adhesive film specifically involves rinsing the pre-cured adhesive film with hot water to remove water-soluble impurities from the adhesive film. In step (S4), the water-soluble impurities refer to at least one of the coagulant, emulsifier, and crosslinking agent remaining in the film; In step (S4), the conditions for heat setting and curing include: heat setting temperature of 100~150 ℃ and time of 20~40 min.